Superpotential of three dimensional N $$ \mathcal{N} $$ = 1 heterotic supergravity - Xenia de Ia Ossa; Magdalena Larfors; Matthew Magill; Eirik E. Svanes (Journal of High Energy Physics)
Abstract We dimensionally reduce the ten dimensional heterotic supergravity action on spacetimes of the form M $$ \mathcal{M} $$ (1, 2) x Y, where M $$ \mathcal{M} $$ (1, 2) is three dimensional maximally symmetric Anti de Sitter or Minkowski space, and Y is a compact seven dimensional manifold with G2 structure. In doing so, we derive the real superpotential functional of the corresponding three dimensional N $$ \mathcal{N} $$ = 1 theory. We confirm that extrema of this functional correspond to supersymmetric heterotic compacti:fications on manifolds of G2 structure in the large volume, weak coupling limit to first order in a'. We make some comments on the role of the superpotential functional with respect to the coupled moduli problem of instanton bundles over G2 manifolds.